2018
DOI: 10.1007/s00262-018-2148-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of PD-1 and other activation markers by CD4+ T cells of young but not old patients with metastatic melanoma

Abstract: The biological behavior of melanoma is unfavorable in the elderly when compared to young subjects. We hypothesized that differences in T-cell responses might underlie the distinct behavior of melanoma in young and old melanoma patients. Therefore, we investigated the circulating T-cell compartment of 34 patients with metastatic melanoma and 42 controls, which were classified as either young or old. Absolute numbers of CD4+ T cells were decreased in young and old melanoma patients when compared to the age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The observed effects of age on the non-suppressive Tregs (fraction 3) and the conventional memory CD25 dim CD4+ T cells (fraction 4) can be attributed solely to the decrease in PD-1 + CD4+ memory T-cell frequencies in older females. Previously, we reported on higher frequencies of PD-1-expressing CD4+ T cells in young, but not old patients with metastatic melanoma, data consistent with the current finding albeit that effects of sex were not documented [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The observed effects of age on the non-suppressive Tregs (fraction 3) and the conventional memory CD25 dim CD4+ T cells (fraction 4) can be attributed solely to the decrease in PD-1 + CD4+ memory T-cell frequencies in older females. Previously, we reported on higher frequencies of PD-1-expressing CD4+ T cells in young, but not old patients with metastatic melanoma, data consistent with the current finding albeit that effects of sex were not documented [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, in this current study, we did not observe differences in expression of CTLA-4 or PD-1 between younger and older memory PB CD4 T cells (albeit from unmatched donor blood samples), potentially highlighting a gut-specific effect. Although previous studies have noted an age-associated increase in CTLA-4 or PD-1 expression on blood CD4 T cells [ 26 29 ], the lack of an apparent age effect observed here is in agreement with a number of other studies [ 30 33 ] and may relate to study populations (e.g. age range, sex) and/or the type of CD4 T cell evaluated (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The naïve T-cell compartment declines 2-5-fold between the ages of 30 and 70 years old, and the ability to establish immunological memory to newly introduced antigens is compromised [28,29]. Furthermore, it was shown that CD4+ T-cells of patients ≤ 50 show more signs of activation, when compared to patients ≥ 65 years of age [30]. These factors can contribute to a less effective T-cell immune response against melanoma cells after immunotherapy with checkpoint inhibition in older adults and elderly as compared to the younger population.…”
Section: Discussionmentioning
confidence: 99%